The Influence of Job Stress, Self-Control, and Organizational Commitment on Cyberloafing Behavior Among Employees in Surabaya. - Wijonarko, Gugus; Wirapraja, Alexander (Jurnal Manajemen, 2024)
Human resources are an important asset in a company, it is assumed that employees who work well will improve the quality of work which has an impact on company productivity. The effort to achieve this is to raise awareness among employees not to spend their working time doing things that are not related to their work, for example by wasting time playing with gadgets during working hours, which is referred to as cyberloafing behavior. The tendency of employees to have this behavior is sometimes caused by a lack of self-control, work stress factors, which causes employees to tend to procrastinate work and make work unfinished. Based on this background, this research aims to determine the influence of self-control, motivation and cyberloafing behavior on the performance of private employees in Surabaya. This research uses a quantitative approach with multiple linear regression methods and uses a sampling method using a purposive sampling method. The population and sample in this research were company employees in Surabaya who were taken randomly. Based on the results of distributing questionnaires and measuring scales using a Likert scale, 127 respondents were obtained. The results of questionnaire data processing show that work stress has no influence on cyberloafing behavior, but the variables of self-control and organizational commitment are proven to influence cyberloafing behavior.